Reliability and Ecological Aspects of Photovoltaic Modules - Gok, Abdülkerim (IntechOpen, 2020)
Photovoltaic (PV) solar energy is expected to be the world's largest source of electricity in the future. To enhance the long-term reliability of PV modules, a thorough understanding of failure mechanisms is of vital importance. In addition, it is important to address the potential downsides to this technology. These include the hazardous chemicals needed for manufacturing solar cells, especially for thin-film technologies, and the large number of PV modules disposed of at the end of their lifecycles. This book discusses the reliability and environmental aspects of PV modules.